Formes de cryoturbation fossiles dans le sud-est du Québec - Dionne, Jean-Claude (Cahiers de géographie du Québec, 1965)
Fossil cryoturbation forms in Southern Québec are reported for the first time. About sixty ice-wedges were observed in unconsolidated Late Pleistocene and Lower Holocene deposits. Other cryoturbation forms such as injections, standing pebbles and strata deformations are also reported. These forms indicate the existence of a periglacial climate, during the Late Wisconsin, in the Appalachian region of Southeastern Québec between 12,500 and 10,000 years (B P )